Scholarly Research Productivity among Otolaryngology Residency Graduates and its Relationship to Future Academic Achievement. (November 2021) - Johnson, Austin L.; Corcoran, Adam; Ferrell, Matthew; Johnson, Bradley S.; Mann, Scott E.; Villwock, Jennifer A.; Ferrell, Sydney; Vassar, Matt
Objective: Scholastic activity through research involvement is a fundamental aspect of a physician's training and may have a significant influence on future academic success. Here, we explore publication rates before, during, and after otolaryngology residency training and whether publication efforts correlate with future academic achievement. Methods: This cross-sectional analysis included a random sample of 50 otolaryngology residency programs. From these programs, we assembled a list of residents graduating from the years in 2013, 2014, and 2015. Using SCOPUS, PubMed, and Google Scholar, we compiled the publications for each graduate, and data were extracted in an independent, double-blinded fashion. Results: We included 32 otolaryngology residency programs representing 249 residents in this analysis. Graduates published a mean of 1.3 (SD = 2.7) articles before residency, 3.5 (SD = 4.3) during residency, and 5.3 (SD = 9.3) after residency. Residents who pursued a fellowship had more total publications ( t 247  = −6.1, P  < .001) and more first author publications ( t 247  = −5.4, P  < .001) than residents without fellowship training. Graduates who chose a career in academic medicine had a higher number of mean total publications ( t 247  = −8.2, P  < .001) and first author publications ( t 247  = −7.9, P  < .001) than those who were not in academic medicine. There was a high positive correlation between residency program size and publications during residency ( r  = 0.76). Conclusion: Research productivity correlated with a number of characteristics such as future fellowship training, the pursuit of an academic career, and overall h-index in this study.